The Witness Blanket : truth, art and reconciliation - Newman, Carey, 1975-; Hudson, Kirstie, 1976- (Orca Books Publishers, 2022)
"This nonfiction book for middle-grade readers, illustrated with photographs, tells the story of the making of the Witness Blanket, a work by Indigenous artist Carey Newman that includes items from every residential school in Canada and stories from the Survivors who donated them."--